Prevalence and Associated Factors of Workplace Violence among Nurses Working in Selected Hospital of Chitwan District - Sedain, Prativa; Sapkota, Keshab Raj; Upadhyay, Hari Prasad (International Journal of Silkroad Institute of Research and Training, 2023)
Background: Workplace violence represents an escalating global challenge that is not only a public health concern but also a significant social issue. The objective of this study is to find the prevalence and associated factors of workplace violence among Nurses of selected hospital. Methods: A hospital based cross- sectional study was carried out among nurses working various hospital of Bharatpur, Chitwan between November 2022 to March 2023. A self-structured questionnaire was used for data collection using Google form. Descriptive and analytical study were used to analyze data. Frequency and percentage were used for categorical data while mean and standard deviation were used for continuous variables. Chi-square test were used association between workplace violence with sociodemographic. p-value <00.05 was considered as statistically significant. Results: Prevalence of work place violence is 43.6% (with 95% CI as 36.7% to 50.40%). Majority of the nurses were victim from verbal abuse (71.91%) followed by physical violence (21.34%) and least (6.75) were suffered from sexual violence. Also, 53.93% violence were occurred inside the health institution Age (p-value=0.017), ethnicity (p-value=0.042), marital status (p-value=0.0209) and position in the hospital (p-value=0.033) was found to be statistically significant with the prevalence of violence. Conclusions: The existence of workplace violence within the healthcare institutions in this region is a pressing issue and a social challenge. Verbal abuse is more prevalent than physical aggression and sexual harassment in the majority of hospitals.